Muslim Political Dynamics Post-Tahkim: A Case Study of the Shiffin War - Muhsin Hariyanto; Mahfud Khoirul Amin (Jurnal Indonesia Sosial Teknologi, 2024)
The Shiffin War, a battle that took place between the Ali bin Abi Talib group and the Mu'awiyah, was a war whose negative impact was felt by Muslims. In fact, in the view of historians, it has resulted in divisions among large groups of Muslims. Although it ended with him which was intended as an attempt to arbitrate between Muslims who were in conflict, it turned out that the effort just stared at the dissatisfaction between them, so three religious-political groups emerged that are still suspected to exist today as a continuation of the phenomenon of division at that time. The rise of Shi'a, Khawarij, and Sunni groups is understood by historians as the impact of the war. Because the awareness of ukhuwah among Muslims has not yet flourished, the division is still felt and there are no significant enough signs to subside, let alone leading to the awakening of ukhuwah consciousness which is marked by the desire to build a dialogue that is built with awareness to bridge the rift that occurs among Muslims, especially from their leaders. Especially for interest groups who see that the tension between Muslims will give them political benefits. In fact, with the right spirit of ukhuwwah, the problem of division between Muslims can be solved.